pyMelt: An extensible Python engine for mantle melting calculations - Matthews, Simon; Wong, Kevin; Gleeson, Matthew (Volcanica, 2022)
Modelling the melting of Earth’s mantle is crucial for understanding the distribution of volcanic activity on Earth and for testing models of mantle convection and mantle lithological heterogeneity. pyMelt is a new open-source Python library for calculating the melting behaviour of multi-lithology mantle and can be used to predict a number of geophysical and petrological observations, including melt productivity, spreading centre crustal thickness, lava trace element concentrations, and olivine crystallisation temperatures. The library is designed to be easily extensible, allowing melting models to be added, different methods for calculating lava chemistry to be applied, and new melting dynamics and properties to be incorporated.